2009
DOI: 10.1183/09031936.00039309
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognostic factors of pulmonary MALT lymphoma

Abstract: Mucosa-associated lymphoid tissue-derived (MALT) lymphoma, a low grade B-cell extranodal lymphoma, is the most frequent subset of primary pulmonary lymphoma. Our objective was to evaluate the initial extent of disease and to analyse the characteristics and long-term outcome of these patients.All chest and pathological departments of teaching hospitals in Paris were contacted in order to identify patients with a histological diagnosis of primary pulmonary lymphoma of the MALT subtype.63 cases were identified. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
195
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(211 citation statements)
references
References 38 publications
10
195
1
5
Order By: Relevance
“…It occurs between the ages of 50 and 80 years, with male predominance; our patient was a 52-year-old male. In the largest clinical series, which included 63 patients with primary pulmonary extranodal MZL, the median age was 60 years and 36% of cases were asymptomatic at time of diagnosis (10). If the patient has symptoms, such as cough, chest pain, or dyspnea, early diagnosis may be possible.…”
Section: Discussionmentioning
confidence: 99%
“…It occurs between the ages of 50 and 80 years, with male predominance; our patient was a 52-year-old male. In the largest clinical series, which included 63 patients with primary pulmonary extranodal MZL, the median age was 60 years and 36% of cases were asymptomatic at time of diagnosis (10). If the patient has symptoms, such as cough, chest pain, or dyspnea, early diagnosis may be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Primary pulmonary lymphomas About half of the patients with primary pulmonary MALT lymphoma are asymptomatic at presentation, and nearly half of these cases are identified accidentally on the basis of abnormal radiological findings [41]. The pulmonary symptoms are nonspecific, like cough, dyspnoea, chest pain and occasional haemoptysis, but are more common than constitutional symptoms, such as weight loss, fever, night sweats or fatigue.…”
Section: Specific Entitiesmentioning
confidence: 99%
“…(7) A study published in 2009 demonstrated the presence of autoimmune disease in 10 of 63 cases of pulmonary MALT lymphoma analyzed. (8) The association between HIV infection and pulmonary MALT lymphoma is unclear, few cases having been reported. (4) The diagnosis is usually difficult and timeconsuming because most individuals are asymptomatic, being diagnosed on the basis of incidental findings on chest X-rays.…”
mentioning
confidence: 99%
“…A recent study reported a five-year survival rate of 90% and a ten-year survival rate of 72%. (8) The most effective treatment has yet to be defined. Various therapeutic regimens have been proposed, including radiotherapy, surgery, chemotherapy, and clinical observation.…”
mentioning
confidence: 99%
See 1 more Smart Citation